Student's Errors in Contructing Passive Voice - Husni, Rauldatul (Universitas Veteran Bangun Nusantara, 2022)
There are many aspects discussed in English Grammar, one of them is passive voice, Students usually found the difficulties when they are learning passive voice, such as lack of vocabulary, less of simple past tense understanding and also they got hard time to distinguish between active and passive voice because they did not know the basic tenses mainly in simple past tense form, so when they were shown the formula of passive voices, especially in simple past tense, they barely understood and confused. This researcher used qualitative method, the design of the research was case study. Researcher analyzed and described the data from the output of the test by using qualitative method. Then,researcher analyzed the students’ errors in transforming the passive voice, and to find out the type of errors, that the students made most in their test in transforming voice of simple past tense, and also to know in terms of verb “be”,correct verb, transformation active sentence into passive sentence and transformation passive sentence into active sentence. The results of this researcher are concludes that the types of error that were made by the in transforming the passive voice from the highest percentage to the lowest are error of misformation, error of omission, and error of misordering. Researcher found that the commonest errors made by the students were the errors of misformation which take up 108 errors or 57%. It i s followed by errors in omission with percentage 23%, and errors in misordering with percentage 20%.